Investigation into the effects of inter-ply sliding during double diaphragm forming for multi-layered biaxial non-crimp fabrics. (November 2021) - Yu, F.; Chen, S.; Harper, L.T.; Warrior, N.A.
Abstract: The effect of inter-ply sliding was investigated for multi-ply Non-Crimp Fabric (NCF) preforms during the Double Diaphragm Forming (DDF) process. A Finite Element (FE) model was employed to investigate the influence of the ply layup sequence and the coefficient of friction between fabric-fabric and fabric-diaphragm interfaces. Simulation results indicate that in-plane fibre compression, caused by dissimilar shear deformation between adjacent plies, can lead to out-of-plane wrinkles, where the wrinkle length is a function of the relative fibre angle at the ply-ply contact interface. The most severe wrinkles occurred when the inter-ply angle was 45° for a multi-ply biaxial NCF preform with a pillar stitch at 45° to the primary yarns. A second parametric study was conducted by incrementally reducing the coefficient of friction at the ply-ply interface. Experiments confirmed that out-of-plane wrinkles are sensitive to the friction resistance between NCF plies and therefore lubricating the fibres can minimise wrinkling defects caused by dissimilar inter-ply deformation.